Silver Linings : Rose Harbor #4 - Macomber, Debbie; King, Lorelei (New York, New York : Random House Audio, 2015)
Struggling with enigmatic Mark's decision to move away, innkeeper Jo Marie welcomes new guests Kellie and Katie, who aim to overcome heartbreak and pursue new chances for love.
Title from container.
Read by Lorelei King; introductory letter read by the author.
Keywords: Hotelkeepers -- Fiction; Interpersonal relations -- Fiction; Man-woman relationships -- Fiction; Audiobooks; Romance fiction